Hatchablility of Broiler Breeder Eggs Sanitized with a Combination of Ultraviolet Light and Hydrogen Peroxide* - Wells, J.B.; Coufal, C.D.; Parker, E.H.M.; Kiess, A.S.; Young, K.M.; McDaniel , C.D. (International Journal of Poultry Science, 2011)
Research has shown that exterior eggshell Aerobic Plate Counts (APC) are greatly decreased using a combination of Ultraviolet Light (UV) and hydrogen peroxide (H2O2). However, it is unknown how this treatment process would impact hatchability. Therefore, the objective of this experiment was to determine if spraying eggs with 1.5% H2O2 followed by UV irradiation for 8 min to reduce eggshell APC would affect hatchability. Eggs from 3 commercial houses (57 wk-old broiler breeders) were collected over 2 d (n = 1,944 eggs). Half were treated with 1.5% H2O2 and UV and the other half served as untreated controls (18 eggs/ tray). At time of treatment, 1 egg was randomly selected from each of 108 trays (n = 54 per treatment) for eggshell APC enumeration on TSA. Remaining eggs were stored at 18.3oC. Prior to set, 1 egg per tray from d 1 of collection was sampled for APC enumeration. The 16 remaining eggs/tray were weighed prior to incubation and at 18 d to determine egg weight loss. At hatch (21.5 d), chick weights were obtained, meconium samples were collected from 18 chicks per incubator and samples were plated on TSA to determine the presence of intestinal microorganisms. A 3 log10CFU/egg reduction in eggshell APC was found for treated eggs when compared to control eggs. At hatch, no differences in chick weight, egg weight loss, positive meconium samples, or hatchability were observed between treatments. In conclusion, UV irradiation for 8 min with 1.5% H2O2 reduced eggshell APC on broiler breeder eggs with no affect on hatchability.